FORMULATION OF SEDIMENTS WITH CHARACTERISTICS OF TROPICAL LOTIC SYSTEMS FOR USE IN ECOTOXICOLOGICAL ASSAYS - Arine, Ana Lúcia Fermino de Oliveira (2016)
Investigation of the dynamics and toxicity of pollutants in natural sediments is hindered by the great complexity of their matrix. Given this difficulty, the objective of this paper was to recommend the formulation of sediments representative of tropical lotic environments, considering their use in ecotoxicological assays. Organic and inorganic fractions were used in different percentages, resulting in five sediment formulations with different grain size proportions (fine, medium and coarse sand, and clay). Measured dissolved oxygen and hardness values were suitable for ecotoxicological assays; however, regarding pH values, only formulations with lower levels of organic matter provided suitable water quality for this purpose (between 6.3 and 7.3), for up to 10 days. These formulations were tested using Hyalella azteca, which confirmed their suitability for use in toxicological tests, since no lethal effects were observed and there were no significant changes in terms of growth and reproduction of the organisms.